Social and cultural aspects of vegetarianism and its perceptions - Aleš Črnič (Družboslovne Razprave, 2012)
The article describes the basic characteristics of vegetarianism and presents the results of an empirical survey conducted on a representative sample of adult inhabitants of the two biggest cities in Slovenia, Ljubljana and Maribor. The main findings include an evaluation of the extent of the researched phenomenon, who and why decides to become a vegetarian and a detailed analysis of perceptions of vegetarianism and veganism among the general population. Special attention is paid to various socio-cultural factors from which the social class structure of Slovenian vegetarians can be estimated, as well as the social distribution of the perception of vegetarianism among Slovenians.